Ta'liq agreement: a proposal for reformation / Nor Fadzlina Nawi - Nawi, Nor Fadzlina (UiTM Kedah, 2003)
And among His Signs is this, that He created for you mates from among yourselves, that ye may dwell in tranquility with them, and He has put love and mercy between your (hearts): verily in that are Signs for those who reflect. [Qur'an 30:21 YusufAH translation].